Brand Betrayal and Its Impact on Consumer Response: A Systematic Literature Review and Future Research Directions - Linuwih, Dara Nurul Idlal; Sunarti, Sunarti; Rahimah, Anni (Wacana Journal of Social and Humanity Studies, 2025)
Brand betrayal is a critical issue that significantly influences consumer responses, often leading to negative behaviors such as brand avoidance, brand switching, brand retaliation, and brand complaints. This study explores the development of literature on brand betrayal and its impact on consumer responses while identifying future research directions and practical strategies for managing these effects. A systematic literature review (SLR) using the PRISMA protocol was conducted, analyzing research from the Scopus database. The data were synthesized through the Theories, Contexts, Methods (TCM), and Antecedents, Decisions, and Outcomes (ADO) frameworks to provide a structured and comprehensive review. The findings reveal that brand betrayal elicits both active responses (retaliation and complaints) and passive responses (avoidance and switching), with emotional attachment playing a key role in shaping consumer reactions. Consumers with stronger emotional bonds to a brand may experience more intense feelings of betrayal, leading to confrontation or silent withdrawal. The study highlights gaps in the current literature, particularly the need for cross-cultural research, longitudinal studies, and deeper exploration of psychological factors influencing consumer behavior post-betrayal. The study concludes that managing brand betrayal requires proactive strategies, including transparent communication, personalized compensation plans, and swift conflict resolution processes. Additionally, understanding the emotional and cognitive processes behind consumer responses is crucial for brands seeking to restore trust, minimize reputational damage, and maintain strong long-term relationships. This research offers key insights for scholars and practitioners, providing guidance on mitigating brand betrayal, fostering long-term brand resilience, and developing adaptive strategies to prevent future occurrences. Keywords: brand betrayal, brand avoidance, brand switching, brand retaliation, brand complaint